AVAILABILITY AND UTILIZATION OF INSTRUCTIONAL MATERIAL IN THE IMPLEMENTATION OF EARLY CHILDHOOD LITERACY CURRICULUM IN PUBLIC SCHOOLS IN ORUMBA SOUTH - Nnabugwu, Juliana O.; Onwuka, Lilian N.; Ugwude, Doris I. (Journal of Early Childhood and Primary Education, 2020)
This study investigated the availability and utilization of instructional materials for the implementation of early childhood literacy curriculum in public schools in Orumba South L.G.A, of Anambra State. Two research questions guided the study. The design was a descriptive survey. The population comprised of 110 pre-school teachers. A sample of 50 pre-school teachers were drawn using simple random sampling techniques. Instrument for data collection was a questionnaire which was developed by the researchers. The instrument was validated by three experts. The reliability of the instrument was determined using Cronbach Alpha Reliability Coefficient which yielded a value of 0.60 and 0.70 with an overall reliability of 0.65. Data collected were analyzed using percentage, mean and standard deviation. The major findings were: that some of the instructional materials were not available for in the implementation of early childhood literacy curriculum and that teachers do not use some of the instructional materials. In conclusion, the teacher do not use instructional materials which would have helped them for gain information’s, think, recall and also assimilate what they have been taught. This hinder the implementation of early childhood literacy curriculum. Based on these findings, recommendation was made: The State Government and Parents Teacher Association (P.T.A) should join hands in providing instructional materials in early childhood education. Workshops and seminars should be organized at times to re-train teachers on how to use instructional materials.
Keywords: instructional materials; literacy; teachers; childhood; Early